Vivienda mínima: solución o conflicto (2019)
The present article exposes a reflection on the precedents, the current and conditions of thehousing in the projects of social interest in Colombia, Where the changes of the residentialarchitecture from the minimization of the inhabitable spaces affect in the transformation inthe way of living of our society. His reality and his implications lead to thinking about thesearch of sustainable alternatives that bear the requirements of the today world in mind butwithout not knowing the fundamental and specific needs of the vulnerable communities. Toknow and to analyze the changes of the popular housing and his relation with the socioeconomic situation of the families that they live, they are the central point of the content.